Does Finance Bolster Superstar Companies? Banks, Venture Capital, and Firm Size in Local U.S. Markets - Alexander Popov (European Central Bank (ECB), 2009)
We study the relative effect of venture capital and bank finance on large manufacturing firms in local U.S. markets. Theory predicts that with venture capital, the firm size distribution should become more stretched-out to the right, but it's ambiguous on the effect of banks on large firms. The empirical evidence suggests that while the average size of firms in the top bin of the firm size distribution has remained unaffected by banking sector developments, it has increased with venture capital investment. We argue that this is due to the emergence of new corporate giants rather than the growth of existing ones.
Keywords: G24; J24; L11; 330; banking; firm size; Venture Capital; Risikokapital; Investmentbank; Betriebsgrößenstruktur; Industrie; USA